Action sounds update the mental representation of arm dimension: contributions of kinaesthesia and agency - Tajadura-Jiménez, Ana; Tsakiris, Manos; Marquardt, Torsten; Bianchi-Berthouze, Nadia (Frontiers in Psychology, 2015)
Auditory feedback accompanies almost all our actions, but its contribution to body-representation is understudied. Recently it has been shown that the auditory distance of action sounds recalibrates perceived tactile distances on one’s arm, suggesting that action sounds can change the mental representation of arm length. However, the question remains open of what factors play a role in this recalibration. In this study we investigate two of these factors, kinaesthesia and sense of agency. Across two experiments, we asked participants to tap with their arm on a surface while extending their arm. We manipulated the tapping sounds to originate at double the distance to the tapping locations, as well as their synchrony to the action, which is known to affect feelings of agency over the sounds. Kinaesthetic cues were manipulated by having additional conditions in which participants did not displace their arm but kept tapping either close (Experiment 1) or far (Experiment 2) from their body torso. Results show that both the feelings of agency over the action sounds and kinaesthetic cues signalling arm displacement when displacement of the sound source occurs are necessary to observe changes in perceived tactile distance on the arm. In particular, these cues resulted in the perceived tactile distances on the arm being felt smaller, as compared to distances on a reference location. Moreover, our results provide the first evidence of consciously perceived changes in arm-representation evoked by action sounds and suggest that the observed changes in perceived tactile distance relate to experienced arm elongation. We discuss the observed effects in the context of forward internal models of sensorimotor integration. Our results add to these models by showing that predictions related to action sounds must fit with kinaesthetic cues in order for auditory inputs to change body-representation.